Marketing plan for the company in the area of information management - Cavaglieri, Marcelo (Seven Editora, 2023)
The market for service provision in the area of standardization of academic work is still little known, with few companies and people specialized in the area. However, in recent years, with more patients entering higher education and the lack of time to dedicate to this activity, the search for this type of service has increased. In this scenario, it is essential to draw marketing strategies to make the company known and be an option for hiring customers. The study was developed at the company MC Normalizações, a provider of formatting services and in the thermalization of academic work according to ABNT standards. A marketing plan was developed to expand its market share, thus being able to retain new customers. To get to know the customers in the public position, a questionnaire was carried out to identify the main needs and the financial disposition to finance this type of service. It was possible to diagnose that the company does not have a consolidated marketing department but practices some marketing actions with customers. This marketing plan will serve as a basis for the new actions proposed here to help the company achieve its mission and vision. Given the results presented, it can be concluded that the focus of marketing actions should be focused on dissemination via the Internet because it is where customers most seek this service, and based on quality, which will help in the dissemination before college colleagues and friends. DOI: https://doi.org/10.56238/devopinterscie-184